2019
DOI: 10.1080/09712119.2018.1561371
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory findings of tracheal wash and bronchoalveolar lavage in normal adult dairy cattle

Abstract: Tracheal Wash (TW) and bronchoalveolar lavage (BAL) are not well documented in adult cattle and published studies were undertaken on diseased animals aiming at isolating the causative agent of respiratory diseases. This study was undertaken to establish the normal cytological and microbiological findings of TW and BAL in normal adult cattle and compare between the laboratory analysis findings of both techniques. Eighteen healthy adult cattle were divided into two groups. BAL was completed the first group (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
6
12
0
Order By: Relevance
“…The low frequency of eosinophils (Abutarbush et al, 2019;Hughes et al, 2003) and mast cells (Hughes et al, 2003;Leclere et al, 2006;Malikides et al, 2003) in BAL and TW from healthy camels of the present study is in agreement with results from other species. Although the diagnostic value of mast cells in BAL and TW are not fully studied (Rossi et al, 2018), we found significantly more mast cells in the BAL from diseased camel, which is similar to results reported for diseased horses (Leclere et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The low frequency of eosinophils (Abutarbush et al, 2019;Hughes et al, 2003) and mast cells (Hughes et al, 2003;Leclere et al, 2006;Malikides et al, 2003) in BAL and TW from healthy camels of the present study is in agreement with results from other species. Although the diagnostic value of mast cells in BAL and TW are not fully studied (Rossi et al, 2018), we found significantly more mast cells in the BAL from diseased camel, which is similar to results reported for diseased horses (Leclere et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Due to limited information about cytological values in camels, the results from the current work were compared with data reported for other species. In our study, the total cell count of BAL in healthy camels was similar to results reported for the bovine BAL cytology (Abutarbush et al, 2019). Similar to other species, including cattle, horses, and donkeys (Abutarbush et al, 2019;Hoffman, 2008;Rossi et al, 2018;Shawaf, 2019), respiratory diseases in camels were associated with increased total cell count in the BAL fluid.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Different diagnostic tools will provide different results for both culture-dependent and culture-independent methods. In cattle, tracheal lavage samples had drastic differences in cytological findings compared to bronchoalveolar lavage due to the location of the respiratory tract sampled (trachea vs. bronchioles), and tracheal lavages had higher na-sopharyngeal contamination [15]. Further, cultures of deep oral swabs are not appropriate surrogates to tracheal lavage samples in dogs, as each resulted in different isolates [16].…”
Section: Introductionmentioning
confidence: 99%